Information architecture of the national platform for volunteer work: evaluation study (The International Journal of Educational Sciences and Arts, 2025)
This study aims to assess the compatibility of the information architecture of the National Platform for Volunteer Work with the proposed information architecture evaluation criteria. The study adopts A descriptive approach, utilizing content analysis and A case study method. Data was collected using A checklist tool developed for this study, comprising four main criteria: (1) the standard for organizing and providing information which includes two aspects: structure &organizing, and design & usability; (2) the standard for information access, covering search and navigation; (3) the standard for information service provision, focusing on electronic services; and (4) the standard for information security and reliability. The study yielded several key findings, the most notable of which are: the information services standard was fully met (100%), ranking highest, followed by the organization and provision of information standard (79.4%), the information access standard (66.7%), and finally, the security standard (54.5%). Overall, the quality of the platform's information architecture was evaluated at (73.2%), classifying it as very good based on the study's evaluation criteria. Based on these findings, key recommendations were proposed, including Enhancing accessibility and user experience by activating assistive tools such as screen readers font enlargement, and color adjustments for individuals an interactive design to ensure compatibility across all devices and ease of use. Strengthening information security and reliability by implementing A comprehensive strategic plan that includes periodic security assessments and user data Protection and increase trust in the platform.
Keywords: Information Architecture; National Platform for Volunteer Work; Volunteer Work; Electronic Information Services; Access to Information; Organization and Availability of Information; Information Security